2018
DOI: 10.1136/bmjopen-2017-019481
|View full text |Cite
|
Sign up to set email alerts
|

Research priorities in health communication and participation: international survey of consumers and other stakeholders

Abstract: ObjectiveTo identify research priorities of consumers and other stakeholders to inform Cochrane Reviews in ‘health communication and participation’ (including such concepts as patient experience, shared decision-making and health literacy).SettingInternational.ParticipantsWe included anyone with an interest in health communication and participation. Up to 151 participants (18–80 years; 117 female) across 12 countries took part, including 48 consumers (patients, carers, consumer representatives) and 75 professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 46 publications
0
52
0
2
Order By: Relevance
“…The lack of standard definitional boundaries of what constitutes digitally-enabled public participation in health research relates to a diversity of approaches, e.g. citizen science, community-based participatory research (CBPR), action research, patient and public involvement (PPI), and crowdsourcing, among other approaches [15,23,76].…”
Section: Challenges and Limitationsmentioning
confidence: 99%
“…The lack of standard definitional boundaries of what constitutes digitally-enabled public participation in health research relates to a diversity of approaches, e.g. citizen science, community-based participatory research (CBPR), action research, patient and public involvement (PPI), and crowdsourcing, among other approaches [15,23,76].…”
Section: Challenges and Limitationsmentioning
confidence: 99%
“…First, it contributes to the literature on providing a detailed process to address research priority setting for YAABCS, as the literature suggests that priority setting between researchers and stakeholders may improve research relevance and value. 11,12 Second, we use an innovative patient-centred storytelling approach to effectively engage YAABC survivors. Storytelling is deeply rooted in African American culture.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, this was expressed in terms of access to educational support, social acceptance and life and community participation. The focus on being equipped for self-management, partnership with clinicians and being empowered to make informed decisions about treatment were reflected in the research priorities, which are similar to those identified in a survey of stakeholder priorities for communication and participation 26. The research questions and themes focused on parents/caregivers were primarily about strengthening ability to cope and impact on families.…”
Section: Discussionmentioning
confidence: 99%